2021
DOI: 10.3390/brainsci11060704
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Difficulties with Speech Fluency and Language Skills in a National Age Cohort of Children with Down Syndrome

Abstract: The present study (a) addressed difficulties in speech fluency in children with Down syndrome and typically developing children at a similar non-verbal level and (b) examined the association between difficulties with speech fluency and language skills in children with Down syndrome. Data from a cross-sectional parent survey that included questions about children’s difficulties with speech fluency, as well as clinical tests from a national age cohort of 43 six-year-olds with Down syndrome and 57 young typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…Translocation is another cause of DS, which occurs when one chromosome is attached to another during the fragmentation of chromosome 21. In contrast, chromosome 21 non-disjunction causes mosaicism, resulting in an additional chromosome copy in one of the cells (Naess et al, 2021); these factors vary from child to child and affect speech and language development. According to Erin et al (2019), moderate to extreme cognitive disability is also linked to DS.…”
Section: Introductionmentioning
confidence: 99%
“…Translocation is another cause of DS, which occurs when one chromosome is attached to another during the fragmentation of chromosome 21. In contrast, chromosome 21 non-disjunction causes mosaicism, resulting in an additional chromosome copy in one of the cells (Naess et al, 2021); these factors vary from child to child and affect speech and language development. According to Erin et al (2019), moderate to extreme cognitive disability is also linked to DS.…”
Section: Introductionmentioning
confidence: 99%
“…Examining speech fluency, Naess et al [ 2 ] found significantly greater difficulties with fluency in a group of children with DS with an average age of 6 years compared to typically developing children with a similar level of nonverbal cognitive functioning. Poorer performance in speech fluency was associated in the study with lower language skills.…”
mentioning
confidence: 99%